Sex disparities and dyslipidemic control in a coronary rehabilitation program. (1st January 2023) - Proença, Tânia; Pinto, Ricardo Alves; Carvalho, Miguel Martins; Rocha, Afonso; Dias, Paula; Macedo, Filipe
Abstract: Lipid control is one of the most important secondary cardiovascular prevention targets. Although cardiovascular disease is the most common cause of death in both sexes, women are less likely to receive guideline-recommended secondary prevention medications. To compare sex disparities in dyslipidemia control in a secondary prevention population, we retrospectively analysed all patients who participated in a Coronary Rehabilitation Program (CRP) after an acute coronary syndrome (ACS) from January 2011 to October 2019. Of a total of 881 patients enrolled, mean age 55.0-year-old, 16.1% were female. At hospital admission, females and males had similar mean LDL-levels. Female patients received more high intensity therapy during follow-up (67.8% vs 53.9% at baseline, p  = 0.015; 75.6% vs 59.0% after CRP, p  = 0.003; and 79.8% vs 65.1% at 1-year-follow-up, p  = 0.007). At the end of the CRP, male patients exhibit a better control of LDL [82.0 vs 75.6 mg/dL, t(597) = 2.4, p  = 0.016)] with 12.8% vs 16.4% below 55 mg/dL and 29.8% vs 44.5% below 70 mg/dL ( p  = 0.008). At 1-year follow-up, both sexes exhibited similar LDL-control thanks to a worsening control of the male population (81.9 vs 80.6 mg/dL, t(540) = 0.52, p  = 0.605). Only 13.3% of females had LDL below 55 mg/dL (vs 12.9%, p  = 0.921) and 32.5% below 70 mg/dL (vs 37.0%, p  = 0.432). This real-life study showed that guideline recommended LDL target is not achieved in the majority of patients. Unlike other reports, there were more women receiving more potent anti-dyslipidemic therapy. Nevertheless, women showed a poor control of LDL-concentration after three months of ACS and a similar control after 1-year. Highlights: It is very difficult to achieve an adequate lipid control, even under a close follow-up and a structured CRP. Women represent a minority of patients performing CRP. Unlike other reports, in our cohort, women received more potent anti-dyslipidemic therapy. Women showed a poor control of LDL-concentration after three months of ACS even under more potent anti-dyslipidemic therapy.